Exchanges of nitrogen and phosphorus across the sediment-water interface influenced by the external suspended particulate matter and the residual matter after dredging. (March 2019) - Liu, Cheng; Du, Yiheng; Yin, Hongbin; Fan, Chengxin; Chen, Kaining; Zhong, Jicheng; Gu, Xiaozhi
Abstract: Dredging is frequently implemented for the reduction of internal nitrogen (N) and phosphorus (P) loadings and the control of eutrophication. Residuals during dredging activities and external pollution loadings after dredging both commonly contribute to influence the effectiveness of dredging and have been widely discussed. In the current study, the exchanges of N and P across the sediment-water interface (SWI) to these two factors were compared in a six-month field incubation experiment. The results showed that the continuous deposition of external suspended particulate matter (SPM) led ammonium nitrogen (NH4 + N) and soluble reactive phosphorus (SRP) fluxes across the newly formed SWI to increase by factors of 4.16 and 12.71, respectively, while residual material caused the same fluxes to increase by factors of 2.06 and 5.06. Both the deposition of external SPM and the residual matter led to higher increase of the fluxes of P across the SWI than those of the fluxes of N across the SWI after dredging. The SPM easily adsorbed P in the water due to extensive adsorption of water soluble organic matter (consisting primarily of easily-decomposed humic-like substances), iron, and aluminum. However, the decomposition of organic matter in the SPM after the deposition on the dredged sediment accelerated the dissolution of redox-sensitive P and organic P across the SWI after dredging. Both the increase in the fluxes of N and P across the SWI would further increase the concentrations of N and P in the overlying water and thereby aggravate the eutrophication status in lakes. More frequent dredging operations might be necessary to reduce the fluxes of N and P from the sediment due to the continuous influence of the external SPM and the residual matter. Graphical abstract: Image 1 Highlights: SPM increased the concentrations of FeP, Org-P, and OM after dredging. SPM led to 4.16- and 12.71-times increases in NH4 + N and SRP fluxes. SPM led to much higher increases in N and P fluxes than did residuals. SPM and residuals led to higher increase in P flux than that of N. Influence of the SPM and residual matter might increase the frequency of dredging. Abstract : The deposition of external SPM led to higher increase in the diffusive fluxes of N and P across the SWI than the residual after dredging, especially for the fluxes of P.